Alignment and Normalization of Mass Spectrometry Data Using the Hydrophobicity Index - Skvortsov, V.S.; Voronina, A.I.; Rybina, A.V. (Biomedical Chemistry: Research and Methods, 2024)
This paper presents a program for the alignment of data from mass spectrometry experiments by retention time on a chromatographic column. The program uses the experimentally obtained data set as a reference against which the alignment procedure is performed. The primary advantage of this approach consists in its capacity to align data sets that had significant variations in both peptide composition and substance amount, such as individual fractions derived from multivariate separation. To illustrate this, two datasets were employed. The first dataset contains data obtained after multivariate separation, while the second dataset exhibited comparable peptide composition across all samples. The second dataset was used to assess the efficacy of the alignment program in normalizing signal intensity between individual samples. The results were compared with the normalization results obtained by the Progenesis LC-MS program. The normalization multipliers obtained for 22 of the 24 samples exhibited good correlation with those calculated by the Progenesis LC-MS (R² = 0.68). The program is freely available at http://lpcit.ibmc.msk.ru/AlignRT.